2014
DOI: 10.1021/nn406263m
|View full text |Cite
|
Sign up to set email alerts
|

Billion-Fold Increase in Tip-Enhanced Raman Signal

Abstract: A billion-fold increase in the Raman signal over conventional tip-enhanced Raman spectroscopy/microscopy (TERS) is reported. It is achieved by introducing a stimulating beam confocal with the pump beam into a conventional TERS setup. A stimulated TERS spectrum, closely corresponding to its spontaneous TERS counterpart, is obtained by plotting the signal intensity of the strongest Raman peak of an azobenzene thiol self-assembled monolayer versus the stimulating laser frequency. The stimulated TERS image of azob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 31 publications
2
58
0
Order By: Relevance
“…The latter leads to homodyning with the incoming probe wave. Wickramasinghe et al [109] used the field enhancement at the sharp gold tip of a scanning tunnelling microscope to locally increase the stimulated Raman scattering efficiency.…”
Section: Plasmonic Antennas For Fwmmentioning
confidence: 99%
“…The latter leads to homodyning with the incoming probe wave. Wickramasinghe et al [109] used the field enhancement at the sharp gold tip of a scanning tunnelling microscope to locally increase the stimulated Raman scattering efficiency.…”
Section: Plasmonic Antennas For Fwmmentioning
confidence: 99%
“…[31] Wickramasinghe et al demonstrated high sensitivity in stimulated TERS, reporting billion-fold enhancement of an azobenzene thiol band when compared to spontaneous TERS. [32] While significant advancements have been made in the field, some issues remain unresolved. For example, high peak powers within individual laser pulses cause intense electromagnetic fields and likely heat at the tip-sample junction, potentially affecting the stability of molecules in the enhancing region.…”
Section: Temporal Resolutionmentioning
confidence: 99%
“…First tunneling to a gold surface has been shown to be an effective method to enhance Raman of molecular species placed on gold [66]. Second tunneling is a known method to investigate plasmonic optical effects [67]. Third tunneling is a good method to induce carriers in semiconductors.…”
Section: The Feedback Mechanismmentioning
confidence: 99%